A new generic synonym in the Reduviinae of Australia, with an updated key to genera (Heteroptera: Reduviidae) - Swanson, Daniel R. (Zootaxa, 2015)
The monotypic genus Horciniella Miller, 1958 is considered a junior synonym of Archilestidium Breddin, 1900 (new synonymy), resulting in the following taxonomic change for its type species: Archilestidium variabile (Miller, 1958) (new combination). The evidence supporting this conclusion and the new composition of the genus are discussed at length. Updated keys to the reduviine genera of Australia and the Australian species of Horcinia Stål, 1874 are included. Habitus images as well as a new distributional record are provided for several Australian reduviines.